Effectiveness of Blended Learning in the Mathematics Curriculum on Self-Efficacy and Academic Motivation of Sixth-Grade Students - Poursaberi, Roghayeh (Iranian Journal of Educational Sociology, 2026)
Purpose: The objective of this study was to examine the effectiveness of implementing blended learning in the mathematics curriculum on sixth-grade students’ self-efficacy and academic motivation.Methods and Materials: This applied research employed a quasi-experimental pretest–posttest design with a control group. The statistical population consisted of all sixth-grade elementary students in Kermanshah during the 2025–2026 academic year. A sample of 30 female students was selected through convenience sampling and randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received eight sessions of blended learning in mathematics over one month, while the control group received traditional instruction. Data were collected using the Mathematics Self-Efficacy Questionnaire (4 items, 4-point Likert scale) and Harter’s Academic Motivation Scale (33 items, 5-point Likert scale). Reliability coefficients using Cronbach’s alpha were 0.90 and 0.91, respectively. Data were analyzed with SPSS-26 using descriptive statistics and multivariate analysis of covariance (MANCOVA).Findings: Results of the multivariate analysis of covariance demonstrated a statistically significant difference between the experimental and control groups in posttest scores of self-efficacy and academic motivation after adjusting for pretest scores (F = 23.145, p = 0.001). Students in the experimental group showed significantly higher self-efficacy and academic motivation compared to the control group, indicating the positive impact of blended learning on both psychological variables.Conclusion: Blended learning in the mathematics curriculum significantly enhances students’ self-efficacy and academic motivation by providing flexible, interactive, and supportive learning environments. These findings highlight the potential of blended learning to improve affective and cognitive outcomes in elementary mathematics education.